Effects of novel thermotropic liquid crystalline polyester with aryl‐ether linkages on the processability and properties of poly(ether ether ketone)s fibers. Issue 2 (26th July 2012) - Wu, Ting; Liu, Pengqing; Wang, Xiao; Zeng, Luxian; Ye, Guangdou; Xu, Jianjun
Abstract A series of composite fibers based on poly(ether ether ketone)s (PEEK) and a novel thermotropic liquid crystalline polyetherarylates (PEAR) with the aryl‐ether linkages, have been prepared by melt spinning. The impact of PEAR on PEEK is investigated by rheological measurements, differential scanning calorimetry, thermal gravimetric analysis, wide angle X‐ray diffraction and scanning electron microscope, orientation degree test and mechanical properties test, etc. The results show that the flowing curves of the blends can be divided into three regions: the first shear thinning region, the shear thickening region, and the second shear thinning region; meanwhile, the PEAR can function as a processing aid by reducing the viscosity of PEEK, thus the processing can be carried out at relatively low temperatures. Although, they are partially compatible, the mechanical properties of the post‐treatment fibers have been improved by 14% after adding 2% PEAR to PEEK. The crystallinity of the as‐spun fibers increases from 22.47 to 42.10%, suggesting that PEAR can act as nucleating agent. Regretfully, both of the initial degradation temperatures and the maximal degradation temperatures decrease with the increase of the PEAR content. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013